Can Steroid Response in Idiopathic Childhood Nephrotic Syndrome be Predicted? A Single Center Quasi-Experimental Study - Rehman, Madeeha; Asghar, Ali; Ehsan, Afshan; Aziz, Madiha; Khatri, Sabeeta; Hashmi, Seema (Pakistan Armed Forces Medical Journal, 2022)
Objective: To predict the role of clinical risk factors and urinary β2-microglobulin levels as a biomarker for steroid-resistant nephrotic syndrome.Study Design: Quasi-experimental study.Place and Duration of Study: Paediatric Nephrology Department, Sindh Institute of Urology and Transplantation, Karachi Pakistan, from Jun 2019 to Nov 2020.Methodology: All children (3 months to 12 years) with either first episode or relapse of the nephrotic syndrome were included. A stored urine sample was used on 100 patients with steroid-sensitive (group-1) and 35 patients with steroid-resistant nephrotic syndrome (group-2). In addition, histopathology of all patients with steroid-resistant nephrotic syndrome was recorded.Results: Both groups and those who had focal segmental glomerulosclerosis were compared and analysed to evaluate the predictability of steroid response. There was a significant association in both groups for microscopic haematuria, hypertension, heavy proteinuria (urine spot protein to creatinine ratio >10 g/g) and increased β2-microglobulin levels (> 3× normal) as individual risk factors (p